Modelling the kinetics of color and texture changes of Dabai (Canarium odontophyllum Miq.) during blanching - Shamsudin, Rosnah; Ariffin, Siti Hajar; Zainol @ Abdullah, Wan Nor Zanariah; Azmi, Nazatul Shima; Abdul Halim, Arinah Adila (MDPI, 2021)
Dabai (Canarium odontophyllum Miq.) is a fruit that is often eaten by first blanching in hot water to make the flesh creamier and softer, before it is served as a snack or side dish. In this study, Dabai fruit was blanched at different temperatures between 60 and 100 °C, with an increment of 10 °C, for up to 10 min, and the kinetics of quality changes (color and texture) were studied. Kinetic models that were assessed for changes of color and texture were zero-order, first-order, and fractional conversion model. The results showed that L parameter had no change throughout the blanching process, while parameters a*, b*, chroma (C), and total color difference (TCD) resulted as significantly increased as the temperature and duration of blanching increased. However, the change of firmness was not significant due to minor changes of firmness as the temperature and time increased. In terms of kinetic models, zero and fractional-conversion order well described the changes of a* parameter; while zero, first and fractional conversion well described parameters b*, C and TCD. Change of firmness did not fit with zero or first-order. All of the kinetic models obeyed the Arrhenius equation. Thus, the fitted kinetic models can be used to design the blanching process of Dabai fruit.